THE IMPACT OF BRAND IMAGE ON CUSTOMER - Andhry Quodvultdeus Darmawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In the current development, the theory of customer satisfaction considered as a key to marketing concept. Some researchers believe that customers’ satisfaction could drive a business to the success (Bennett and Rundle-Thiele, 2004). According to Kotler and Keller (2009), satisfaction is the summary feeling resulted from comparing a product performance to the expectation. A customer will be satisfied if the performance matches expectation. On the other side, a customer will be dissatisfied if the performance fails to meet expectation. Martisiute et al. (2010) theorized that the success of a company does not only depend on the ability to attract new customers. Retaining satisfied customers is beneficial because it needs less cost than to attract the new ones. One of the important strategies to achieve customer satisfaction is branding strategy.